ӘЖИНИЯЗ ШАЙЫР ӘЎЛАДЛАРЫНЫҢ ХРОНОЛОГИЯЛЫҚ ШЕЖИРЕСИНИҢ ДҮЗИЛИЎИ - Есебаев, М.М. (SCIENCE and SOCIETY, 2024)
A chronological genealogy of the descendants of Ajiniyaz Kosibay uli has been drawn in this article. Currently, it is determined that they live in the cities of Shumanay, Kanli-kol, Kungrat, Nukus and addresses are indicated.